Bioinformatics Approach Reveals the Insecticidal Potential of Geosmin by its Binding Efficacy with the Odorant Binding Protein of Various Insects - T. Kirthika; S. Nandhini; R. Gayathri; A. Praveena (Cutting Edge Research in Biology Vol. 3, 2023)
Geosmin is an earthy and muddy odorant compound produced by some bacteria present in the moist soil. It is evident that it has great influence on insects. This study aims to analyze the effectiveness of geosmin binding to the odorant binding protein and its insecticidal activity against various insects. The detection of smell in insects such as moth, aphids is aided by the olfactory receptors which are localized in the antenna. The olfactory receptors possess odorant binding protein. The inactive form of this protein turns active when a chemical or odorant compound binds to it. The active form of the protein triggers a signal transduction cascade that results in neuronal firing and brain-centered perception of the odorant, which in turn triggers the appropriate behavioral response of the insects. As a result of this observance, the analysis of interaction between odorant compound geosmin and insects is done. Technologically, by the action of the odorant compound Geosmin, the influence of insects on the crops can be reduced. Ultimately the usage of insecticides in the agricultural field can be reduced. Hence, in the present study different olfactory receptor proteins of various insects collected from NCBI database and phylogenetic analysis was done using MEGA11 software. The protein structure was modeled using SWISS MODEL SERVER and the molecular interaction was analyzed using AUTODOCK software. The results showed that the among the selected insect species, Geosmin has more influence on Galeruca Daurica and has lowest binding energy of about -8.73kcal/Mol.